Proposta de iniciativa de lei de inovação para Santarém-Pa - Fonseca, Andre Silva da (Universidade Federal do Oeste do Pará, 2023)
This proposed Santarém Innovation Law initiative 'borns' from the activities developed in the Professional Master's Degree course in Intellectual Property and Technology Transfer for Innovation (PROFNIT) at the Federal University of Oeste do Pará (UFOPA) as a return to the production of knowledge and identifying bottlenecks and opportunities in ICTs, aiming at their use by society and contributing to development and economic growth at the local level, in order to improve the living conditions of the population and regional development. Thus, the discussions lead to the proposed Law initiative that points to the Municipal Innovation Policy as a legal framework, whose objective is to structure and provide sufficient skills to raise awareness, disseminate and implement the innovative culture and sustainable development in Santarém, by guiding the articulation and activities of the municipal government with the Research and Development Institutions, the Business Sector and with the various agents that make up the Innovation Ecosystem. To fulfill this objective, an applied research was carried out on a documentary and bibliographic basis, where the Innovation Policy of Salvador, Law nº 9534 of 11 August 2020, Law of Innovation of Maceió, Law nº were identified as innovative sources. 6.902/2019 and the Innovation Law of Florianópolis, Complementary Law No. 432, of May 7, 2012. It should be noted that, according to the logical bases of the investigation, the method used was the deductive one, which is part of the general analysis for the particular one to achieve the knowledge/desired proposal. Thus, it was considered that the implementation of the proposed Municipal Innovation Law could be one of the main instruments of support and encouragement to the productive sector, scientific knowledge and innovative enterprises and sustainable development in Santarém.